La carte conceptuelle comme outil favorisant l'apprentissage de la modélisation des bases de données - Lynda Farza
The concept map is considered as a stimulating tool in teaching, learning and assessment. Several studies have shown the importance of integrating the concept map in different domains and contexts of teaching / learning. In this paper we study the use of the concept map as a tool favoring the learning of data modeling in an introductory database course which is provided to novice students. Our purpose is to motivate students, to get them interested in the modeling of the databases and to increase the efficiency of their learning. We reported also the results of the study we conducted during the 2015/2016 academic year, with 50 first-year university students from our institution. These students with similar initial training, without any prior knowledge in data modeling or conceptual map, were divided into two groups : one as an experimental group having followed the teaching with integration of the concept map in the process modeling and the other as a control group having followed the same teaching without use of the concept map. We have studied the conceptual schema produced by the students of the two groups during the achievement test in order to detect and analyze the errors made by the two groups. Student scores were also analyzed to see if there was a significant difference between the scores of the two groups. This study revealed statistically significant differences between the scores of the two groups in favor of the experimental group.